(untitled) (Experimental biology, 2015)
Data on studying of a role of phytoameliorants are provided in this article at restoration of properties of the petropolluted soils. Statistical processing of results of phytomelioration on experimental sites of a field Kumkol by experience options with soil ameliorants is carried out: the petropolluted soil, the soil without pollution (control), application of NP fertilizers, with bentonite clay, with a rice peel, with mix of all ameliorants and with biocoal. The most effective species of plants phytoameliorants are defined